Together and apart in Brzezany : Poles, Jews, and Ukrainians, 1919-1945 - Redlich, Shimon, 1935- (Bloomington ; Indianapolis : Indiana University Press, 2002)
"Shimon Redlich draws on the historical record, his own childhood memories, and interviews with Poles, Jews, and Ukrainians who lived in the small eastern Polish town of Brzezany to construct this account of the changing relationships among the town's three ethnic groups before, during, and after World War II. He details the history of Brzezany from the prewar decades (when it was part of independent Poland and members of the three communities remember living relatively amicably "together and apart"), through the tensions of Soviet rule, the trauma of the Nazi occupation, and the recapture of the town by the Red Army in 1945. Historical and contemporary photographs of Brzezany and its inhabitants add immediacy to this fascinating excursion into history brought to life, from differing perspectives, by those who lived through it."--Amazon
My return -- Close and distant neighbors -- The good years, 1919-1939 -- The Soviet interlude, 1939-1941 -- The German occupation, 1941-1944 -- The aftermath, 1944-1945 -- Their return.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Redlich, Shimon, -- 1935-; Redlich, Shimon, -- 1935-; Berez͡hany (Ukraine) -- Ethnic relations; Berez͡hany (Ukraine) -- History -- 20th century; 15.70 history of Europe; SOCIAL SCIENCE -- Anthropology -- Cultural; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Europe -- Eastern; Ethnic relations; Ukraine -- Berez͡hany; Juden; Polen; Ukrainer; Berezhany; Oekraïeners.; Joden; Polen (volk); Jews -- Ukraine -- Berzhany -- History; Juden; Ukrainer; 1900-1999; Geschichte 1919-1945; Electronic books; Autobiography; autobiographies (literary genre); Autobiographies; History; Autobiographies; Autobiographies; Online-Publikation.